Perspectives on Human Nature and Implications for Research in the Behavioural Sciences - Eketu, Continue Anddison (International Journal of Emerging Trends in Social Sciences, 2018)
This paper examined the perspectives of human behaviour as a precursor to determine the methodological preference for inquiry into the knowledge of its complex and intricate nature. The paper identified some fundamental taxonomies of action, expressed in human action, social action, purposive action, environmentally constrained action, and emergent process action. These constitute perspectives on action that are broadly categorized into prospective and retrospective perspectives on action. The prospective view holds that meaning of action is constructed and known before the action, while the retrospective perspective presupposes that meaning of action can only be constructed and known after the action. However, the bipolar views tend to elicit different methodologies from opposing intellectual domains. The paper contended that for the sake of robust social knowledge, mixed methods defined in methodological pluralism should be adopted in inquiry related to the behavioural sciences.